Komunikasi Terapeutik Pada Lansia Yang Ada Di Panti Sosial Di Indonesia: Literatur Review - Rifqi Priatama; Lukman Hakim; Aditya Nanda Anugrah; Dini Nur Alpiah; Gibran Kemenangan Jihad (Kampus Akademik Publiser, 2024)
Therapeutic communication is an important element in the care of elderly people in social institutions, influencing their quality of life, emotional well-being and social interactions. However, effective implementation of therapeutic communication in this context is often faced with challenges such as communication barriers and lack of adequate training for social home staff. This research aims to explore the importance of therapeutic communication in the context of elderly people in social institutions in Indonesia, as well as to highlight the relationship between therapeutic communication practices and the quality of life, emotional well-being and social relationships of elderly people. The research method used was a literature review involving relevant quantitative and qualitative studies from 2023 to 2024. Data was analyzed from various scientific articles and related studies that discussed therapeutic communication and its impact on the elderly in social institutions. The research results show that effective therapeutic communication plays an important role in improving the quality of life of elderly people in social institutions. The studies conducted revealed a positive relationship between therapeutic communication practices and reducing anxiety levels, improving quality of life, and strengthening social relationships in the elderly. These findings underscore the urgency for the development of practice guidelines and further research to improve the implementation of more effective therapeutic communication in social institutions in Indonesia.